Impact of parental and healthcare professional concern on the diagnosis of pediatric sepsis: a diagnostic accuracy study - Sever, Zoe; Schlapbach, Luregn J.; Gilholm, Patricia; Jessup, Melanie; Phillips, Natalie; George, Shane; Gibbons, Kristen; Harley, Amanda (Frontiers in Pediatrics, 2023)
Objective: The Surviving Sepsis Campaign recommends systematic screening for sepsis. Although many sepsis screening tools include parent or healthcare professional concern, there remains a lack of evidence to support this practice. We aimed to test the diagnostic accuracy of parent and healthcare professional concern in relation to illness severity, to diagnose sepsis in children. Design: This prospective multicenter study measured the level of concern for illness severity as perceived by the parent, treating nurse and doctor using a cross-sectional survey. The primary outcome was sepsis, defined as a pSOFA score >0. The unadjusted area under receiver-operating characteristic curves (AUC) and adjusted Odd`s Ratios (aOR) were calculated. Setting: Two specialised pediatric Emergency Departments in Queensland Patients: Children aged 30 days to 18 years old that were evaluated for sepsis Intervention: None Main Results: 492 children were included in the study, of which 118 (23.9%) had sepsis. Parent concern was not associated with sepsis (AUC 0.53, 95%-CI 0.46-0.61, aOR 1.18; 0.89-1.58) but was for PICU admission (OR 1.88, 95%-CI 1.17-3.19) and bacterial infection (aOR 1.47, 95%-CI 1.14-1.92). Healthcare professional concern was associated with sepsis in both unadjusted and adjusted models (nurses: AUC 0.57, 95%-CI-0.50, 0.63, aOR 1.29, 95%-CI 1.02-1.63; doctors: AUC 0.63, 95%-CI-0.55, 0.70, aOR 1.61, 95%-CI 1.14-2.19). Conclusions: While our study does not support the broad use of parent or healthcare professional concern in isolation as a pediatric sepsis screening tool, measures of concern may be valuable as an adjunct in combination with other clinical data to support sepsis recognition.